Risk of major vascular events in patients without traditional risk factors after transient ischemic attack or minor ischemic stroke: an international prospective cohort - Uchiyama, Shinichiro; Hoshino, Takao; Minematsu, Kazuo; Meledje, Marie-Laure; Charles, Hugo; Albers, Gregory W; Caplan, Louis R; Donnan, Geoffrey A; Ferro, José M; Hennerici, Michael G.; Molina, Carlos; Rothwell, Peter M; et al. (European stroke journal, 2025)
Introduction: To investigate the clinical characteristics in patients without traditional risk factors (TRFs) after transient ischemic attack or minor ischemic stroke, who were recruited in the TIAregistry.org. - Patients and methods: A total of 3847 patients were analyzed. TRFs included hypertension, diabetes, hypercholesterolemia, current smoking, and atrial fibrillation. Background characteristics and outcomes at 1 and 5 years in patients without TRFs were compared to those in patients with TRFs. The primary outcome was major cardiovascular event (MACE), which was non-fatal stroke, non-fatal acute coronary syndrome, or vascular death. To evaluate the causes, we applied the ASCOD (atherosclerosis, small vessel disease, cardiac pathology, other causes or dissection) grading system. - Results: One-year risk of MACE (5.3% vs 6.3%, hazard ratio (HR) 0.84, 95% confidence interval (CI) 0.53-1.31) was comparable between patients without TRFs (n = 402) and those with TRFs (n = 3445). Five-year risk of MACE was significantly lower in patients without TRFs than in those with TRFs (7.9% vs 13.9%, HR 0.57, 95% CI 0.39-0.82). In patients without TRFs, causal atherosclerosis was a potent risk factor (HR 5.67, 95% CI 2.68-12.02) and ipsilateral extra- or intra-cranial arterial stenosis was only significant predictor of MACE (interaction p = 0.0046) at 5 years. - Conclusion and discussion: The 5-year risk of MACE was lower in patients without TRFs than those with TRFs, although a certain level of risk persisted in the absence of TRFs. The most significant predictor of MACE in patients without TRFs was arterial stenosis.